Recent advances and new perspectives in mitochondrial dysfunction - Cecilia Giulivi; Kezhong Zhang; Hirofumi Arakawa (Scientific Reports, 2023)
Abstract In the last decade, there has been an increased appreciation for mitochondria as central hubs in diverse processes, such as cellular energy, immunity, and signal transduction. As such, we have become aware that mitochondrial dysfunction underlies many diseases, including primary (mutations in genes encoding mitochondrial proteins) and secondary mitochondrial diseases (mutations in non-mitochondrial genes critical for mitochondrial biology), as well as complex diseases with mitochondrial dysfunction (chronic or degenerative diseases). Evidence suggests that mitochondrial dysfunction may often precede other pathological signs in these disorders, further modulated by genetics, environment, and lifestyle.